ASTORECA PALACE, RECOVERY OF A SYMBOL OF THE NITRATE SPLENDOR OF THE 19TH CENTURY. Enhancement of Historical Monument Tarapacá Region, Chile - Mendoza Cornejo, Marlene B. (2023)
Heritage assets have been essential in politics, especially in the 19th century where building a national heritage was key to legitimizing order and the nation. Recently, global and local debates on the cultural paradigm have arisen that challenge the hegemonic view of heritage and instigate reflections on how cultural expressions are perceived. A significant example of this architecture is the Astoreca Palace, a symbol of the bourgeoisie linked to the nitrate industry. After its construction, it became state property and became a regional administration, and later transformed into an informal cultural space. This research proposes the recovery of this heritage building. To do this, it is argued around the existing values ​​of the property, its history and the strategies to enhance it to respond to the contemporary needs of citizens for its recognition as a meeting place with local history.